Grasshopper sparrows on the move: patterns and causes of within-season breeding dispersal in a declining grassland songbird - Williams, Emily Jean (Kansas State University, 2016)
Dispersal is a behavior common to virtually all taxa with important consequences for gene flow, demography, and conservation. Mobile animals such as birds frequently engage in breeding dispersal, but the factors shaping this behavior are not well understood. In mid-continental grasslands, preliminary evidence suggested that Grasshopper Sparrows (Ammodramus savannarum) engaged in breeding dispersal within a single breeding season. This intriguing pattern shaped my research questions: (1) what are the patterns of within-season breeding dispersal in Grasshopper Sparrows? (2) why do some individual sparrows disperse, and others do not? and (3) what shapes settlement decisions following dispersal? I tested hypotheses based on spatial and temporal variation in nest predation, nest parasitism, and food availability. I studied Grasshopper Sparrows at 18 experimentally-managed watersheds with different fire and grazing regimes at Konza Prairie Biological Station during 2013-2015. To describe patterns, I combined re-sighting of 779 marked individuals, territory mapping, and radio-telemetry to quantify territory densities, turnover, and dispersal distances. To determine if nest predation or nest parasitism affected dispersal, I monitored the fate of 223 nests. I estimated food intake rates using plasma metabolites, and prey availability using sweep sampling. Densities of territorial Grasshopper Sparrows varied seasonally in management-specific ways. Turnover was remarkably high, with over half of territorial males being replaced each month. Over a third of males changed territories within-season, dispersing 0.1-9 km between breeding attempts. Dispersal decisions were related to past nest predation, but not nest parasitism. Dispersal likely yields fitness benefits, as sparrows that dispersed increased their chances of nest survival by 23% relative to site-faithful individuals. However, food availability did not affect settlement decisions. My study provides the first evidence of within-season breeding dispersal in Grasshopper Sparrows, and represents one of few tests of alternative hypotheses explaining dispersal decisions of songbirds. My results are consistent with a growing literature on the role of predation shaping dispersal, but suggest, somewhat surprisingly, that food is not important in post-dispersal habitat selection. High dispersal capacity coupled with adaptability to temporal and spatial change may be typical of grassland songbirds, implying that demographic studies and management decisions must consider their mobility for conservation.
Keywords: Dispersal; Grasslands; Grasshopper Sparrow; Within-season breeding dispersal; Movement ecology; Habitat selection